Fear of Missing Out dengan Nomophobia pada Mahasiswa : Kus Hanna Rahmi, Candias Cathartika Sukarta - Hanna Rahmi, Kus; Cathartika Sukarta , Candias (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
The use of smartphones in students can cause various kinds of negative impacts such as feelings of anxiety when away from smartphones. Students experience feelings of anxiety based on the fear of missing out on information and activities that other people do, this causes feelings of anxiety away from smartphones which is often called nomophobia. This study aims to determine whether there is a relationship between fear of missing out with nomophobia tendencies in psychology students. by using a total of 147 respondents from the psychology faculty of University Bhayangkara. The method used in this study is correlational with the aim of seeing the relationship of the two variables studied, using SPSS version 25. The results of the calculation of the correlation test R = 0.664, with a significance level of p = 0.00 (p>0.05). These results show that fear of missing out is positively related to nomophobia in psychology students at University Bhayangkara. Suggestions for students in particular are to be able to regulate the use of smartphones as an effort to prevent nomophobia tendencies which will have a negative impact on health and social interaction, so that students will find it easier to understand. interact and have a calm feeling.